The Paradoxes of Delusion : Wittgenstein, Schreber, and the Schizophrenic Mind - Sass, Louis A. (Book collections on Project MUSE., 2018)
Insanityu2014in clinical practice as in the popular imaginationu2014is seen as a state of believing things that are not true and perceiving things that do not exist. Most schizophrenics, however, do not act as if they mistake their delusions for reality. In a work of uncommon insight and empathy, Louis A. Sass shatters conventional thinking about insanity by juxtaposing the narratives of delusional schizophrenics with the philosophical writings of Ludwig Wittgenstein.